Mediating Role of Entrepreneurial Attitudes in the Relationship between Adversity Quotient, Self-Efficacy, and Entreprenurial Intention - Ambari, Rukmani Dewi; Permana, Ida Bagus Gede Adi; Arina, Nidya Ayu (International Journal of Psychosocial Rehabilitation, 2020)
This study aim to find mediation effect of entrepreneurial attitudes on relationship between adversity quotient, entrepreneurial self efficacy and entrepreneurial intention. Using part time undergraduate students as sample that currently are juggling with work demand and academic pressure. The result shows that entrepreneurial attitudes are partially mediates both relationship between adversity quotient, entrepreneurial self- efficacy and entrepreneurial intention. Students who like challenges and always looking for new ways to develop are more likely to become entrepreneurs